1997
DOI: 10.1002/(sici)1097-4628(19971205)66:10<1943::aid-app10>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and static-dynamic mechanical behavior of mica-reinforced linear and star-branched polybutadiene composites

Abstract: Physical properties of mica-reinforced linear (LPB) and star-branched polybutadiene (SPB) composites have been studied with special reference to the effect of silane coupling agent, degree of crosslinking, and degree of mica loading, as well as the molecular architecture of polybutadienes. Tensile properties increase and swelling decreases with addition of mica for linear polybutadiene. Star-branched polybutadiene shows a reverse behavior, especially beyond 5% of mica. The improvements in mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
3
6
0
Order By: Relevance
“…Thereby, the formation of charge transfer complex is inhibited by the surface coverage that means a decrease in cure time 11, 12. Similar observations, increase in the rate of vulcanization of mica reinforced polybutadiene composites and glass bead filled polyester composites with surface silanization, were also reported by Nugay et al,13 Lee and Han,11 and Shieh and Hsu,12 respectively.…”
Section: Resultssupporting
confidence: 69%
“…Thereby, the formation of charge transfer complex is inhibited by the surface coverage that means a decrease in cure time 11, 12. Similar observations, increase in the rate of vulcanization of mica reinforced polybutadiene composites and glass bead filled polyester composites with surface silanization, were also reported by Nugay et al,13 Lee and Han,11 and Shieh and Hsu,12 respectively.…”
Section: Resultssupporting
confidence: 69%
“…Results of using the DMA technique to characterise interfacial effects in particulate and fibre-reinforced polymer composites have been reported in the literature [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most of the studies were carried out in temperature sweeps at fixed frequencies (isochronal conditions) near transition regions of the matrix, specially covering the glass transition region.…”
Section: Introductionsupporting
confidence: 76%
“…23 Figure 3 presents elongation-at-break values of the composites. Similar to the behavior observed for the polybutadiene composites, 11 addition of mica increases the ductility of the samples. Sim- observed that with the addition of two-dimensional fillers such as mica in the polypropylene matrix mica-reinforced polypropylene becomes more and more ductile, leading to higher elongation.…”
Section: Swelling Of Compositesmentioning
confidence: 99%